THE EFFECT OF INFLATION, INTEREST RATE, AND GROSS DOMESTIC PRODUCTS ON THE PROFITABILITY OF SHARIA BANKING IN INDONESIA (Sharia Banking Financial Reports 2014-2018) - Hidayat, Imam; Alwahidin, Alwahidin; Aspiani, Tetin (AGUSPATI Research Institute, 2020)
This study aims to determine the effect of inflation, interest rates, and gross domestic product on Islamic banking's profitability in Indonesia. The research approach is a quantitative research using data in the form of time series in the 2014-2018 Islamic bank financial statements. The method used is descriptive statistical analysis, classic assumption test, and multiple regression equation tests using the SPSS 21 computer program. Based on the results of the research conducted, it can see that partially shows that inflation has a significant influence on the Profitability of Islamic Banking in Indonesia with smaller t counts from t table that is equal to 0.219 smaller than 2.040 and a significant value of 0.828 smaller than 0.999, the interest rate variable partially has a significant effect on the Profitability of Islamic Banking in Indonesia with t count smaller than t table that is -0.918 smaller than 2.040. A significant value of 0.365 is smaller than 0.999. The GDP variable significantly affects the Profitability of Islamic Banking in Indonesia with a count smaller than the t table that is equal to 0.371 smaller than 2.040 and a significant value of 0.713 smaller than 0.999. So it was concluded that the ups and downs of Sharia Banking Profitability are influencing by Inflation, Interest Rates, and Gross Domestic Product.